Menopause and postmenopausal hormone therapy and risk of hearing loss. Issue 9 (September 2017) - Curhan, Sharon G.; Eliassen, A. Heather; Eavey, Roland D.; Wang, Molin; Lin, Brian M.; Curhan, Gary C.
Abstract: Objective: Menopause may be a risk factor for hearing loss, and postmenopausal hormone therapy (HT) has been proposed to slow hearing decline; however, there are no large prospective studies. We prospectively examined the independent relations between menopause and postmenopausal HT and risk of self-reported hearing loss. Methods: Prospective cohort study among 80, 972 women in the Nurses' Health Study II, baseline age 27 to 44 years, followed from 1991 to 2013. Baseline and updated information was obtained from detailed validated biennial questionnaires. Cox proportional-hazards regression models were used to examine independent associations between menopausal status and postmenopausal HT and risk of hearing loss. Results: After 1, 410, 928 person-years of follow-up, 18, 558 cases of hearing loss were reported. There was no significant overall association between menopausal status, natural or surgical, and risk of hearing loss. Older age at natural menopause was associated with higher risk. The multivariable-adjusted relative risk of hearing loss among women who underwent natural menopause at age 50+ years compared with those aged less than 50 years was 1.10 (95% confidence interval [CI] 1.03, 1.17). Among postmenopausal women, oral HT (estrogen therapy or estrogen plus progestogen therapy) was associated with higher risk of hearing loss, and longer duration of use was associated with higher risk ( P trend < 0.001). Compared with women who never used HT, the multivariable-adjusted relative risk of hearing loss among women who used oral HT for 5 to 9.9 years was 1.15 (95% CI 1.06, 1.24) and for 10+ years was 1.21 (95% CI 1.07, 1.37). Conclusions: Older age at menopause and longer duration of postmenopausal HT are associated with higher risk of hearing loss. Abstract : Supplemental Digital Content is available in the text